Pharmacokinetics and Pharmacodynamics of Tegoprazan Coadministered With Amoxicillin and Clarithromycin in Healthy Subjects - Ghim, Jong-Lyul; Chin, May Chien; Jung, Jinah; Lee, Jiwon; Kim, Seokuee; Kim, Bongtae; Song, Geun Seog; Choi, Young-Kyung; Shin, Jae-Gook (Journal of clinical pharmacology, 2021)
This clinical trial was conducted to evaluate the pharmacokinetics and pharmacodynamics of tegoprazan when coadministered with amoxicillin/clarithromycin in healthy subjects. Cohort 1 was an open-label, randomized multiple-dose study to evaluate the mutual interaction of tegoprazan and amoxicillin/clarithromycin on the disposition of 3 tested drugs including tegoprazan M1 metabolite and 14-hydroxyclarithromycin (14-OH-clarithromycin). Cohort 2 was an open-label, randomized, active-controlled, parallel multiple-dose study to compare the intragastric pH profile after multiple oral doses of 50 or 100 mg tegoprazan coadministered with amoxicillin/clarithromycin 1000/500 mg for 7 days and pantoprazole-based triple therapy as the comparator arm. The coadministration of tegoprazan with amoxicillin/clarithromycin increased C (2.2-fold) and AUC (2.7-fold) of tegoprazan and M1 (2.1- and 2.2-fold for C and AUC , respectively) compared with administration of tegoprazan alone. The C and AUC of 14-OH-clarithromycin increased by 1.7- and 1.8-fold, respectively; the disposition of amoxicillin and clarithromycin were not significantly changed. On days 1 and 7 of treatment, tegoprazan-based therapies (both 50- and 100-mg therapies) maintained pH above 6 for more than 88% of the 24-hour period, which was significantly longer compared with pantoprazole-based therapy. Tegoprazan either alone or in combination with amoxicillin/clarithromycin was well tolerated in healthy subjects. In conclusion, the exposure of tegoprazan was increased after coadministration of amoxicillin/clarithromycin, which led to increase pharmacodynamic response measured by intragastric pH compared with tegoprazan alone. Therefore, tegoprazan-based triple therapy would be effective therapeutic regimen to manage intragastric pH in terms of gastric or duodenal ulcers healing, treatment of gastroesophageal reflux disease, and Helicobacter pylori eradication.